NILAI-NILAI PENDIDIKAN AKHLAK MAHMUDAH DALAM NOVEL KETIKA CINTA BERTASBIH KARYA HABIBURRAHMAN EL SYIRAZY - Nur Azizah; Deswalantri (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Morals are very important in life. In this regard, the role of Islamic religious education among Muslims is included in the category of embodiment of the ideals of Islamic life in preserving and transforming Islamic values to the next generation personally. Morals guided by the light of Allah will give birth to a straight and directed ethics. As a result, moral development education should be provided in formal, non-formal, and informative teaching and education. The purpose of this study is to describe the values of moral education in the novel when love is blessed by Habiburrahman El Shirazy. This research method is a type of library research where data is collected from relevant written documents The purpose of this research is to solve problems that require a critical and indepthstudy of the relevant library materials. Nasal data comes from primary andsecondary sources. The results show that the values of moral education in thenovel when love is blessed by Habiburrahman El Shirazy are: morality towardsAllah and His Messenger, which consists of gratitude, patience, and salawat,morals. towards parents, which consists of gentle words to parents, moralstowards oneself which consists of hard work, high ideals. Morals towards fellowhuman beings consisting of humility. Based on the research that has been carriedout, it is concluded that in the novel when love is blessed by Habiburrahman ElShirazy contains the values of mah easy moral education including: 1) moralstowards Allah and His Messenger, 2) morals towards parents, 3) morals towardsoneself, 4 ) morality towards fellow human beings